Kreativitas Guru Pak Dalam Meningkatkan Minat Belajar Siswa Pada Masa Pandemi Covid-19 - Relly Poluan; Heldy Rogahang; Ribka Munte; Bryan Kaurouw (Pascasarjana IAKN Manado, 2021)
This study aims to describe the creativity of PAK teachers at SMTK Baitani Pulutan, Pulutan district, Talaud Regency in increasing students' interest in learning during the Covid-19 pandemic, the inhibiting factors faced, and efforts to overcome them. This research is a qualitative research with a descriptive approach. The data obtained comes from the results of observations, interviews, and documentation. The data analysis techniques in this study include three steps, namely data reduction, data presentation, and drawing conclusions The results of this study show that: 1) The creativity carried out by PAK teachers in increasing student interest in learning, namely related to the use of learning media, applying teaching strategies by explaining lessons first and then giving assignments, as well as showing videos related to the material presented; 2) Factors inhibiting the creativity of PAK teachers in increasing interest in learning, namely the lack of school facilities such as LCD learning media, the pandemic situation that does not allow carrying out discussions or study groups, the lack of seriousness of learning from students, and also the absence of efforts from teachers to be more creative in increasing student interest in learning; 3) PAK teachers are looking for other fun creative media that can be used such as pictures, posters, videos, and also PAK teachers teaching outdoors. PAK teachers must further enhance and develop creativity in teaching in schools in order to increase students interest in learning in participating in PAK learning